Clinical evaluation, imaging studies, indications for cytologic study and preprocedural requirements for duct brushing studies and pancreatic fine-needle aspiration: The Papanicolaou Society of Cytopathology Guidelines - Adler, Douglas (Medknow Publications & Media Pvt Ltd, 2014)
The Papanicolaou Society of Cytopathology has developed a set of guidelines for pancreaticobiliary cytology including indications for endoscopic ultrasound (EUS) and fine-needle aspiration (FNA) biopsy, techniques for EUS-FNA, terminology and nomenclature to be used for pancreaticobiliary disease, ancillary testing and postbiopsy management. All documents are based on expertise of the authors, literature review, discussions of the draft document at national and international meetings and synthesis of online comments of the draft document. This document selectively presents the results of these discussions. This document summarizes recommendations for the clinical and imaging work-up of pancreatic and biliary tract lesions along with indications for cytologic study of these lesions. Prebrushing and FNA requirements are also discussed.